Implication of Individual Plan for Professional Development (IPPD) on Teachers’ Professional Development and Career Advancement - Osias Kit T. Kilag; Irene A. Bariquit; Cynthia G. Glipa; Renan A. Renan A. Ignacio; Geraldine U. Alvez; Ritchel T. Guilot; John Michael Sasan (Basic and Applied Education Research Journal, 2023)
The research was conducted to determine the needs of teachers for their continuous professional development and to create an individual professional development plan for this aim. This study utilized qualitative investigation; the Heideggerian Phenomenology design was employed. This study seeks to comprehend the phenomenon from the participant's point of view and through their experiences. In total, twenty teachers from Philippine schools were interviewed. The interviews were verbatim captured on tape and then transcribed. Three main themes emerged from the analysis of the data: (a) IPPD gives greater insights and improves performance; (b) IPPD allows putting into practice the appropriate trainings and seminars attended; and (c) IPPD impacts students’ learning and behaviour. Based on the findings, professional development can encourage teachers' creativity and help break up the monotony of daily work. Offering regular professional development can also assist individuals in acquiring fresh knowledge and viewpoints that may influence how they approach their work. Furthermore, it is critical to give financial support for teachers' professional growth, as seen by the difficulties they face.